Critique, social media and the information society - Fuchs, Christian; Sandoval, Marisol (New York : Routledge, 2014)
"In times of global capitalist crisis we are witnessing a return of critique in the form of a surging interest in critical theories (such as the critical political economy of Karl Marx) and social rebellions as a reaction to the commodification and instrumentalization of everything. On one hand, there are overdrawn claims that social media (Twitter, Facebook, YouTube, etc) have caused uproars in countries like Tunisia and Egypt. On the other hand, the question arises as to what actual role social media play in contemporary capitalism, crisis, rebellions, the strengthening of the commons, and the potential creation of participatory democracy. The commodification of everything has resulted also in a commodification of the communication commons, including Internet communication that is today largely commercial in character. This book deals with the questions of what kind of society and what kind of Internet are desirable, how capitalism, power structures and social media are connected, how political struggles are connected to social media, what current developments of the Internet and society tell us about potential futures, how an alternative Internet can look like, and how a participatory, commons-based Internet and a co-operative, participatory, sustainable information society can be achieved"--
Includes bibliographical references.
Keywords: Information society; Social media